Smoking and nicotine dependence in relation to depression, anxiety, and stress in Egyptian adults: A cross-sectional study - Naglaa A El-Sherbiny; Asmaa Y Elsary (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Much research has found that smoking is one of the major risk factors for a variety of physical diseases and mental disorders; however, few studies have been conducted on smoking in Egypt. Furthermore, to the researcher's best knowledge, no study in Egypt has compiled data on smoking prevalence, motives, and levels of nicotine dependency. In order to fill in this gap, the current study has attempted to summarize the situation and construct an accurate picture of smoking in Egypt. MATERIALS AND METHODS: This cross-sectional study included 2000 Egyptian adults in Fayoum through a multistage cluster sampling technique. For data collection, the Socioeconomic Status Scale was deployed. In addition, Depression, Anxiety, Stress Scale (DASS), the Modified Reasons for Smoking Scale (MRSS), and Fagerstrom Test for Nicotine Dependence (FTND) were used. Data analysis performed using SPSS version 22.0. For qualitative data, Chi-square test was used to determine statistical significance. Bivariate Pearson correlation was used to test for the association between quantitative variables. RESULTS: Of the total sample of 2000 adults, 40.4% had anxiety and 24.3% had stress, and 19.5% showed severe to extremely severe level of depression. For MRSS, tension reduction or relaxation was found in 46.5% adults while 9.8% had high level of nicotine dependence. There was a statistically significant association between psychometric disorders, on one hand, and both smoking motivation and nicotine dependence, on the other (P < 0.001). The DASS score had a statistically significant correlation with age, smoking duration, nicotine dependence level, and MRSS subscales. CONCLUSION: Smoking is linked to psychological symptoms and shows a moderate to high level of nicotine dependence, with a higher level of dependency, smoking pleasure, stress reduction/relaxation, and hand-mouth movement as motives for smoking. Furthermore, there was a correlation between nicotine dependence, on one hand, and depression and stress on the other.